PAVEL VILIKOVSKY IS GONE. OVER THE AUTHOR'S LAST PROSE RAJc JE PREČ - Machala, Lubomír (Bohemica Olomucensia, 2023)
A brief recapitulation of Pavel Vilikovský's life and work prefaces an analytical-interpretive commentary on his last published prose RAJc je preč, which can be considered a personal review of one's real life and creativity, which - thanks to its approach - goes beyond the personal framework. In this piece of work, Vilikovský (re)presents and critically reflects his life experience, joys, traumas, loves (more precisely: intimate relationships), friendships, and creativity very openly and in detail. All of this using his usual creative instruments, i.e. intellectual scepticism, grotesque optics, irony, self-irony and inimitable mastery of language and composition.
Keywords: Pavel Vilikovský; last prose; analysis and interpretation